(untitled) (Research, Society and Development, 2022)
The article presents, through the scientific literature, how maternal and child care units were organized to guarantee or not the companion during labor, delivery, and puerperium during the Covid-19 pandemic. This is an integrative review, carried out from August 2021 to February 2022, in which scientific articles from the LILACS, BVS and PUBMED databases were used, in English and Portuguese, using the descriptors in Portuguese: rooming-in; patient companions; maternity hospitals; Covid-19 and in English: rooming-in care, medical chaperons, maternity hospitals, Covid-19, regarding the rights and changes in the presence of the companion in maternal and child care units due to the Covid-19 pandemic, published in January 2020 to March 2021. 194 studies were found, of which 13 were excluded due to duplicity and after the selection and eligibility steps, 176 studies were excluded, totaling a sample of 05 articles. In general, most studies restricted the presence of companions, in some, in cases of suspected or confirmed pregnant and postpartum women with Covid-19, but some institutions will prohibit regardless of confirmation, symptoms or not. As a result of the theoretical analysis, observation, studies and reflections that allow us to recognize that the presence of someone they know would be more beneficial than harmful for these women, since going through this birth process alone was considered lonely by them, generating emotional discomforts.